Restricting Sugar or Carbohydrate Intake Does Not Impact Physical Activity Level or Energy Intake Over 24 Hours Despite Changes in Substrate Use: A Randomised Crossover. (14th June 2022) - Hengist, Aaron; Davies, Russell; Rogers, Peter; Brunstrom, Jeff; Van Loon, Luc; Walhin, Jean-Philippe; Thompson, Dylan; Koumanov, Françoise; Betts, James; Gonzalez, Javier
Abstract: Objectives: To determine the effects of dietary sugar or carbohydrate restriction on physical activity energy expenditure, energy intake, and physiological outcomes across 24 hours. Methods: In a randomised, open-label crossover design, twenty-five healthy men (n = 10) and women (n = 15) consumed three diets over a 24-hour period: moderate carbohydrate and sugar content (MODSUG = 50% carbohydrate [20% sugars], 15% protein, 35% fat); low sugar content (LOWSUG = 50% carbohydrate [<5% sugars], 15% protein, 35% fat); and low carbohydrate content (LOWCHO = 8% carbohydrate [<5% sugars], 15% protein, 77% fat). Postprandial metabolic responses to a prescribed breakfast (20% EI) were monitored under laboratory conditions before an ad libitum test lunch, with subsequent diet and physical activity monitoring under free-living conditions until blood sample collection the following morning. Results: The MODSUG, LOWSUG and LOWCHO diets resulted in similar mean [95%CI] rates of both physical activity energy expenditure (771 [624, 919] vs 677 [565, 789] vs 802 [614, 991] kcal·d −1 ; p = 0.29] and energy intake (2071 [1794, 2347] vs 2195 [1918, 2473] vs 2194 [1890, 2498] kcal·d −1 ; p = 0.34), respectively. The LOWCHO condition elicited the lowest glycaemic and insulinemic responses to breakfast ( p < 0.01) but the highest 24-h increase in LDL-cholesterol ( p < 0.001), with no differences between the MODSUG and LOWSUG treatments. Leptin concentrations were decreased over 24-h of consuming LOWCHO relative to LOWSUG ( p < 0.01). Conclusions: When energy density is controlled for, restricting either sugar or total dietary carbohydrate does not modulate physical activity level and energy intake over a 24-hour period despite large changes in metabolism. Funding Sources: This study was supported by The Rank Prize Funds and Kenniscentrum Suiker and Voeding.